The relationship between Islamic creed and social skills and students’ emotional well-being - Muslimin, Zidni Immawan; Nurwahyuni, Ika Lestari (Universitas Ahmad Dahlan, 2025)
This study investigates the extent to which Islamic creed (ʿAqīdah) and social skills are associated with students’ emotional well-being. Utilizing a quantitative correlational design, the study involved 197 students aged 15–19 years from a state-funded Islamic secondary school. Participants were selected through cluster random sampling. Three validated instruments were employed: the Emotional Well-Being Scale based on Keyes’ conceptual framework (α = 0.803), the Islamic Creed Scale adapted from Al-Banna’s model (α = 0.893), and the RECS Social Skills Scale developed by Mantzouranis et al. (α = 0.896). Data were analyzed using multiple linear regression. The results revealed that Islamic creed and social skills jointly demonstrated a significant positive relationship with emotional well-being (p = 0.006). Further analysis showed that Islamic creed independently had a significant positive association with emotional well-being (p = 0.005), whereas social skills did not show a statistically significant effect (p = 0.142). These findings highlight the central role of religious belief in supporting adolescents' emotional well-being within faith-based educational contexts.